IDENTITY, AFFECT, AND CULTURAL CITIZENSHIP IN DIASPORIC CONTEXT - Shilpi Saxena; Diksha Sharma (Trames, 2022)
Over the years, the study of transnational affect and emotion has become an emergent field of migrant narratives. Drawing on the notion of affect as a useful paradigm for analyzing emotional or bodily responses, the present article explores the affective and emotional dimensions of migration in connection with the emerging paradigm of âcultural citizenshipâ, which plays a crucial role in the construction of diasporic affiliations. In doing so, it provides new cartographies of mapping the emotional geographies of migration that are crucial to the understanding of the nature, intensity and affect of the migratory experience. Examining the nexus between emotion and migration, this article explores the cultural dimension of citizenship, and how cultural acts and practices that immigrants employ provide new forms of belonging and identification in relation to increasingly complex patterns of transnational migration.